Multi-Poly-Silicon-Layer-Based Spot-Size Converter for Efficient Coupling Between Silicon Waveguide and Standard Single-Mode Fiber - Weifeng Jiang; Niharika Kohli; Xiaohan Sun; B. M. Azizur Rahman (IEEE Photonics Journal)
A novel spot-size converter (SSC) incorporating a phase-matched polycrystalline-silicon (Poly-Si) multilayer is proposed and optimized for efficient nanophotonic coupling, which can be fabricated by using the complementary metal–oxide–semiconductor (CMOS) compatible process and can be directly integrated. An efficient algorithm, combining the rigorous $H$ - field-based full-vectorial finite-element method and the least square boundary residual method, is developed for the design optimization of the SSC. The use of simple single-layer and multilayer Poly-Si-based SSCs is investigated, in which the coupling process and phase matching for isolated and composite waveguides are also carried out. The coupling loss can be reduced to 2.72 dB by using an 11-Poly-Si-layer-based SSC. The on-chip integrated SSC opens up the feasibility of a low-cost passive-aligned fiber-pigtailed electronic–photonic integrated-circuit (PIC) platform.